2019
DOI: 10.1101/638247
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parameter tuning differentiates granule cell subtypes enriching the repertoire of retransmission properties at the cerebellum input stage

Abstract: The cerebellar granule cells (GrCs) form an anatomically homogeneous neuronal population which, in its canonical description, discharges regularly without adaptation. We show here that GrCs in fact generate diverse response patterns to current injection and synaptic activation, ranging from adaptation to acceleration of firing. Adaptation was predicted by parameter optimization in detailed GrC computational models based on the available knowledge on GrC ionic channels. The models also predicted that accelerati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 74 publications
(130 reference statements)
1
4
0
Order By: Relevance
“…with TRPM4 channels, which are primarily described in PCs (Kim et al, 2009(Kim et al, , 2013Menigoz et al, 2016). Remarkably, our model, derived from previous models (D 'Angelo et al, 2001;Nieus et al, 2006;Diwakar et al, 2009) and upgraded to account for sophisticated mechanisms of spike generation, predicted that TRPM4 currents, first recorded in GrCs, coupled to calmodulin through intracellular Ca 2+ changes, could effectively generate firing acceleration observed experimentally (Masoli et al, 2020b). Remarkably, mossy fiber-GrC synapse simulations showed that fine-tuning of adaptation/acceleration and short-term plasticity generated effective mossy fiber-GrC transmission channels, which could enrich the processing of incoming spike trains and enhance spatiotemporal coding at the cerebellar input stage (Gabbiani et al, 1994), according to the theoretical prediction of the adaptive filter model (Marr, 1969;Dean and Porrill, 2011;Rössert et al, 2015;D'Angelo et al, 2016).…”
Section: The Granular Layersupporting
confidence: 55%
See 3 more Smart Citations
“…with TRPM4 channels, which are primarily described in PCs (Kim et al, 2009(Kim et al, , 2013Menigoz et al, 2016). Remarkably, our model, derived from previous models (D 'Angelo et al, 2001;Nieus et al, 2006;Diwakar et al, 2009) and upgraded to account for sophisticated mechanisms of spike generation, predicted that TRPM4 currents, first recorded in GrCs, coupled to calmodulin through intracellular Ca 2+ changes, could effectively generate firing acceleration observed experimentally (Masoli et al, 2020b). Remarkably, mossy fiber-GrC synapse simulations showed that fine-tuning of adaptation/acceleration and short-term plasticity generated effective mossy fiber-GrC transmission channels, which could enrich the processing of incoming spike trains and enhance spatiotemporal coding at the cerebellar input stage (Gabbiani et al, 1994), according to the theoretical prediction of the adaptive filter model (Marr, 1969;Dean and Porrill, 2011;Rössert et al, 2015;D'Angelo et al, 2016).…”
Section: The Granular Layersupporting
confidence: 55%
“…In contrast to the canonical view describing GrCs as a homogenous population of neurons generating regular firing, our recently published work combining data from simulations and experimental findings on GrC electro responsive properties has identified different subtypes: adapting, non-adapting and accelerating GrCs (Masoli et al, 2020b). Adaptation occurs via Ca 2+ influx through high-threshold Ca 2+ conductance and subsequent increase in Ca 2+ -activated K + currents, causing an after-hyperpolarization potential after a burst of spikes (D'Angelo et al, 1998) whereas acceleration is correlated 2016)].…”
Section: The Granular Layermentioning
confidence: 84%
See 2 more Smart Citations
“…These simulations therefore strongly support the concept that mossy fiber -granule cell plasticity is fundamental to tune the filtering properties of the cerebellar granular layer. The recently discovered granule cell subtypes (adapting, nonadapting and accelerating) may further bias the unit toward high-pass or low-pass filtering depending on the expression of TRPM4 channels 45 .…”
Section: Model Prediction Of Spike Filtering Properties In Granular Lmentioning
confidence: 99%